Fuzzy logic system for BBT based fertility prediction - Mohd Yazed, Muhammad Syukri; Mahmud, Farhanahani; Morsin, Marlia (African Journal Online (AJOL), 2017)
This paper introduce a fuzzy logic system for fertility prediction to improve the BBT technique based on FAM. The development of the fertility prediction system using fuzzy logic is motivated by its ability to conduct a complex relationships that its factors, which can address the issue of imprecision in the fertility prediction. the reference sets of BBT data tested on the fuzzy logic system for the prediction of ovulation and pregnancy, a significant result have been obtained with the accuracy of 95 % and 80 respectively. Besides, this prediction system using fuzzy logic could improve the current practice in the FAM technique by integrating it with an Internet of Things (IoT) technology for automatic BBT charting and monitoring.